We, programmers a chronicle of coders from Ada to AI - Martin, Robert C. (Robert C. Martin Series, 2024)
In We, Programmers, software legend Robert C. Martin--"Uncle Bob"--dives deep into the world of programming, exploring the lives of the groundbreaking pioneers who built the foundation of modern computing. From Charles Babbage and Ada Lovelace to Alan Turing, Grace Hopper, and Dennis Ritchie, Martin shines a light on the figures whose brilliance and perseverance changed the world. This memoir-infused narrative provides a rich human history filled with technical insights for developers, examining the coding breakthroughs that shaped computing at the bit and byte level. By connecting these technical achievements with the human stories behind them, Martin gives readers a rare glimpse into the struggles and triumphs of the people who made modern technology possible. Depression, failure, and ridicule--these pioneers faced it all, and their stories intertwine with the evolution of computing itself as the field evolved from its humble beginnings to the cloud-based AIs of today. With the rise of AI, Martin also explores how this technology is transforming the future of programming and the ethical challenges that come with it.